2020
DOI: 10.1126/sciadv.abb6298
|View full text |Cite
|
Sign up to set email alerts
|

Real-time shaping of entangled photons by classical control and feedback

Abstract: Quantum technologies hold great promise for revolutionizing photonic applications such as cryptography. Yet, their implementation in real-world scenarios is challenging, mostly because of sensitivity of quantum correlations to scattering. Recent developments in optimizing the shape of single photons introduce new ways to control entangled photons. Nevertheless, shaping single photons in real time remains a challenge due to the weak associated signals, which are too noisy for optimization processes. Here, we ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…Once revived, the two photons remain entangled up to an arbitrary propagation distance in the angle-OAM bases. We note that the entanglement revival strategies in turbulence or random media are usually based on adaptive optics techniques ( 31 , 56 , 57 ), which involve feedback mechanisms and thus are quite difficult to implement. On the other hand, in our work, we have shown that entanglement in the angle-OAM bases can be revived simply by further propagating the two-photon field by some distance, without having to use any adaptive optics techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Once revived, the two photons remain entangled up to an arbitrary propagation distance in the angle-OAM bases. We note that the entanglement revival strategies in turbulence or random media are usually based on adaptive optics techniques ( 31 , 56 , 57 ), which involve feedback mechanisms and thus are quite difficult to implement. On the other hand, in our work, we have shown that entanglement in the angle-OAM bases can be revived simply by further propagating the two-photon field by some distance, without having to use any adaptive optics techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we show that the same masks allow restoring and controlling the high dimensional biphoton state transmitted through the ground glass diffuser. Instead of point detectors measuring temporal coincidences between spatially entangled photons [5,6,8], single-photon sensitive cameras are used, allowing the detection of all photons of the images and the measurement of momentum spatial coincidences on the whole set of photons without any prior selection of the photons in time and space coincidence. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To shape the spatial structure of the JPD, most approaches act directly on the down-converted photons, such as wavefront shaping [21,22], quantum interferometers [23,24], metasurfaces [25,26] and rotating diffusers [27]. Recently, partial control of the spatial JPD has been achieved through spatial shaping of the pump beam profile, for example to produce entangled Airy photons [28], compensate for optical aberrations [29], and to influence its OAM [30] and position-momentum degree of entanglement [31,32]. However, a generic method to deterministically control the spatial JPD of entangled photon pairs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%